GENIUS LOCI KAMPUNG BANDAR PEKANBARU - Kaffah, Mahya Fiddini; Ekomadyo, Agus S. (Nature : National Academic Journal of Architecture, 2022)
Abstract_ Kampung Bandar is an old town that became the forerunner of the development of Pekanbaru City. Kampung Bandar is located on the banks of Siak River, a river that is a source of life and a place for people to carry out their daily activities. The existence of the Siak River creates a unique socio-cultural atmosphere for the community. The purpose of this study is to reveal the Genius Loci in Kampung Bandar using the Genius Loci approach proposed by Norberg-Schultz within the framework of architectural phenomenology. The method used in the process of collecting data in this study is a qualitative method. Research shows that the Genius Loci of Kampung Bandar are formed by the community's attachment to the Siak River which is manifested in the form of buildings, traditions, and community activities in daily life. Keywords: Architecture; Genius Loci; Kampung Bandar.